1983
DOI: 10.1016/0304-4157(83)90003-5
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of neutral amino acid transport in mammalian cells

Abstract: BBA - Reviews on Biomembranes 737 (1983) 267-284. doi:10.1016/0304-4157(83)90003-5Received by publisher: 1982-10-06Harvest Date: 2016-01-04 12:22:08DOI: 10.1016/0304-4157(83)90003-5Page Range: 267-28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
182
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(193 citation statements)
references
References 170 publications
10
182
1
Order By: Relevance
“…The amino acid analog MeAIB is an inhibitor and specific substrate for system A amino acid transport and the main transport mechanism for MeAIB uptake is thought to occur via system A [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid analog MeAIB is an inhibitor and specific substrate for system A amino acid transport and the main transport mechanism for MeAIB uptake is thought to occur via system A [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Since [ 11 C]MeAIB has higher selectivity for system A compared to [ 11 C]-2-aminoisobutyric acid ([ 11 C]AIB, another system A substrate) [27,31], [ 11 C]MeAIB is expected to be very useful in system A amino acid transport PET imaging. We have previously reported the utility of [ 11 C]MeAIB in the diagnosis of chest diseases, especially in the differential diagnosis between sarcoidosis and metastasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant amino acid in serum, glutamine is a readily available nutrient for most cells, and is involved in providing nitrogen for synthesis of many amino acids (Caro-Maldonado et al, 2014;Hensley et al, 2013). Several genes associated with amino acid transport and biosynthesis are induced under starvation conditions in various cell types, including B cells (Le et al, 2012;Shotwell et al, 1983). However, despite the fundamental role of necessary nutrients-glucose and glutamine-as building blocks for protein synthesis and substrates for multiple metabolic processes, regulation of uptake and utilization of these two key nutrients during B cell activation is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…lower than normal Correspondence address: M.J. Rennie, Dept of Physiology, University of Dundee, Dundee DDI 4HN, Scotland for glutamine and higher for the branched-chain amino acids (BCAA) [1,2]. In trying to understand these changes we previously investigated the properties of amino acid transport systems of muscle [3][4][5] which we found to be somewhat different from those of other tissues [6]. In particular we found that glutamine was transported by a single carrier whose properties [3][4][5] helped exPlain the normal and abnormal patterns of muscle glutamine distribution.…”
Section: Introductionmentioning
confidence: 99%